Specific music therapy techniques in the treatment of primary headache disorders in adolescents: a randomized attention-placebo-controlled trial - Koenig, Julian; Oelkers-Ax, Rieke; Kaess, Michael; Parzer, Peter; Lenzen, Christoph; Hillecke, Thomas; Resch, Franz (The journal of pain, 2013)
Migraine and tension-type headache have a high prevalence in children and adolescents. In addition to common pharmacologic and nonpharmacologic interventions, music therapy has been shown to be efficient in the prophylaxis of pediatric migraine. This study aimed to assess the efficacy of specific music therapy techniques in the treatment of adolescents with primary headache (tension-type headache and migraine). A prospective, randomized, attention-placebo-controlled parallel group trial was conducted. Following an 8-week baseline, patients were randomized to either music therapy (n = 40) or a rhythm pedagogic program (n = 38) designed as an “attention placebo” over 6 sessions within 8 weeks. Reduction of both headache frequency and intensity after treatment (8-week postline) as well as 6 months after treatment were taken as the efficacy variables. Treatments were delivered in equal dose and frequency by the same group of therapists. Data analysis of subjects completing the protocol showed that neither treatment was superior to the other at any point of measurement (posttreatment and follow-up). Intention-to-treat analysis revealed no impact of drop-out on these results. Both groups showed a moderate mean reduction of headache frequency posttreatment of about 20%, but only small numbers of responders (50% frequency reduction). Follow-up data showed no significant deteriorations or improvements. - Perspective - This article presents a randomized placebo-controlled trial on music therapy in the treatment of adolescents with frequent primary headache. Music therapy is not superior to an attention placebo within this study. These results draw attention to the need of providing adequate controls within therapeutic trials in the treatment of pain.
Gesehen am 09.12.2021